The Relationship Between Food Intake and The Incidence of Chronic Energy Deficiency (CED) In Pregnant-Women of Sugio Public Health Center Lamongan - Fitria, Nuraini; Esyuanik, -; Pipitcahyani, Tatarini Ika; Nurwulansari, Fitria (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
Nutrition of pregnant women must be considered, there will be problems for the mother and fetus if maternal nutrition is not provided properly. The purpose of this study was to determine whether there is a relationship between food intake and the incidence of CED in pregnant women. The sampling method used purposive sampling. The sample of this study was 100 pregnant women. This study was conducted from August 2023 to May 2024. Spearman Rank (Rho) test was used to analyze univariate and bivariate data. The results found a correlation between energy, protein, fat, and carbohydrate intake with a p value of 0.000. This study found that food intake (protein, fat, carbohydrate, and energy) of pregnant women at the Sugio Lamongan Health Center is associated with cases of Chronic Energy Deficiency (CED).